The electroacupuncture-induced analgesic effect mediated by 5-HT(1), 5-HT(3) receptor and muscarinic cholinergic receptors in rat model of collagenase-induced osteoarthritis - Seo, Byung-Kwan (BMC Complement Altern Med, 2016)
BACKGROUND: Osteoarthritis (OA) is an degenerative disease characterized by chronic joint pain. Complementary and alternative treatment such as acupuncture have been utilized to alleviate pain. The objective of this study was to investigate the analgesic mechanisms of electroacupuncture (EA) in the collagenase-induced osteoarthritis (CIOA) rat model. METHODS: Four weeks after inducing CIOA by injecting collagenase solution into the left knee of 5-week-old male Sprague-Dawley rats, 2 Hz and 100 Hz EA on Zusanli (ST 36) was performed. The analgesic effect of EA was evaluated by the tail flick latency (TFL) and paw pressure threshold (PPT) tests. To investigate the analgesic mechanism, serotonergic and muscarinic cholinergic receptor agonists and antagonists were injected 20 min prior to EA and the resultant changes were evaluated by the TFL and PPT tests. RESULTS: EA on Zusanli (ST 36) demonstrated an analgesic effect in the CIOA rat model. The 2 Hz EA treatment showed a significantly greater analgesic effect than the 100 Hz treatment. The analgesic effect of 2 Hz EA was not strengthened by 5-HT1, 5-HT2, 5-HT3, and muscarinic cholinergic receptor agonist pretreatment, was blocked by 5-HT1, 5-HT3, and muscarinic cholinergic receptor antagonist pretreatment, but not blocked by 5-HT2 receptor antagonist pretreatment. CONCLUSIONS: In the CIOA rat model, EA on Zusanli (ST 36) exhibited analgesic effects, and 2 Hz EA resulted in a significantly greater analgesic effect than 100 Hz EA. The analgesic effect of 2 Hz EA was reduced by pretreatment of 5-HT1 receptor, 5-HT3 receptor and muscarinic cholinergic receptor antagonists.